Differences of Seropositivity against Selected Infectious Agents in Relation to Farm Management Characteristics to Broiler Production in Uruguay - Rodriguez, G.; Suzuki, K.; Petruccelli, M.; Trenchi, G.; Giossa, G.; Trenchi, H. (International Journal of Poultry Science, 2010)
The objective of this study was to investigate risk factors, especially for management characteristics associated with the seropositivity of respiratory infectious agents such as avian pneumovirus, Ornithobacterium rhinotracheale, Mycoplasma gallisepticum and Mycoplasma synoviae in broiler chickens on farms in Uruguay. Seventeen farms of broiler chickens (>35 days old) were studied between October 2008 and April 2009, comprised data collection through questionnaire interviews for each study farm, in combination with blood sample collections for each chicken (n = 1861). Of all the 17 study farms, 13, 13, five and nine farms were classified as seropositive against avian pneumovirus, Ornithobacterium rhinotracheale, Mycoplasma gallisepticum and Mycoplasma synoviae, respectively. The seropositivity against Ornithobacterium rhinotracheale in relation to the use of vaccination programmes indicated statistical significance. The farms with the vaccination programmes would be more likely to practise the same or similar sanitary measures, which could contribute to prevent the chickens from various infection. Practice of a sanitary measure would be indicative of a poultry farm to distinguish potential risks of diseases. Key words: Poultry farming operations, questionnaire, South America